The Financial Performance of Foreign Bank Subsidiaries - Boubacar, Hamadou (Indian Journal of Finance, 2011)
The objective of this study is to take into account the organizational characteristics that bind the parent banks and their subsidiary companies to explain the financial performance of banks’ foreign subsidiaries. To this aim, we empirically study the average data (from 2001 to 2005) of a sample of 123 bank subsidiary companies (with or without majority ownership). The results show that the percentage of the capital held by the parent banks, an indicator of its capacity to influence the strategy of subsidiaries, is not without consequence on their performance.